الأنماط الإدارية لمديري المدارس في محافظة شمال الباطنة من وجهة نظر المعلمين وعلاقتها بسلوكهم الإبداعي بسلطنة عمان - أحمد بن عبد الله بن حمد المنوري
This study aimed to determine the prevailing administrative patterns among school principals in Al Batinah North Governorate from the teachers' point of view. The study also aimed to reveal the level of teachers' possession of creative behavior in the northern Al Batinah Governorate in the Sultanate of Oman from their point of view. The objectives of the study also include measuring the correlation between the administrative styles of school principals in Al Batinah North Governorate and their creative behavior in the Sultanate of Oman from the teachers’ points of view. The researcher used the descriptive analytical correlative method to achieve the objectives of the study. A two-axis questionnaire was used; where the first axis was meant to identify administrative patterns, and the second axis was meant to measure the level of teachers' creative behavior. The study population consisted of all male and female teachers in the schools of Al Batinah North Governorate sized (N=10409) from which the random sample was selected which sized (n=375) male and female teachers. The (SPSS) program was also used to analyze the study data. The study reached several findings the most important of which is that the leading administrative pattern among school principals in the North Al Batinah Governorate is the diplomatic administrative pattern with an arithmetic mean of (3.93); It is followed by the democratic administrative style with an arithmetic mean (3.51); It is given by the authoritarian administrative style with an arithmetic mean (3.49); Finally, the chaotic administrative style with an arithmetic mean (3.15). The results of the study showed that teachers practice creative behavior at an average level as a whole, with a mean of (3.43). The results also show that this practice occurs at varying levels; The field of ability to present new ideas and proposals ranked first, then the field of ability to provide innovative solutions to problems and the field of ability to change ranked second. And in the last place came the field of ability to risk. The results also show that there is a positive medium correlation with statistical significance between the administrative styles of school principals in Al Batinah North Governorate and their creative behavior at (r= 0.520); (sig.0.005). The study recommended several recommendations, the most important of which is to promote the footsteps of the diplomatic style and the democratic style as a model for school administration because of their positive results on the creative behavior of teachers. The recommended included avoiding the use of the chaotic pattern in some situations because of its negative impact on the creative behavior of teachers. further recommendations asserted that more effort should be made to provide school principals in the North Al Batinah Governorate in the with theoretical knowledge about administrative patterns, theories and their impact on teachers' creative behavior. The recommendations also included the necessity of paying attention to outstanding teachers by encouraging them to develop creative behavior skills in Al Batinah North Governorate.